Emerging Adult Perceptions of Cannabis Use Based on Age and Sex of User. Issue 4 (August 2021) - Harris-Lane, Laura; Winters, Emily; Harris, Nick
In Canada, emerging adults consume more cannabis than any other age-group. This study examined emerging adults' perceptions of dangerousness, perceptions of negative impacts, and level of disapproval associated with regular cannabis use. An experimental vignette design was utilized to examine the extent to which perceptions differ depending on the age and sex of the user. Participants ( N = 656) were randomly assigned to one of six vignettes and were asked to rate 7 items of perceived dangerousness, perceived negative impacts, and level of disapproval. Significant main effects of age were found on 6 of 7 items, where cannabis use by a 14-year-old was viewed as more dangerous than cannabis use by a 21- and 28-year-old. However, cannabis use by a 21-year-old was not viewed as more dangerous than cannabis use by a 28-year-old. Female cannabis use was perceived as more dangerous than male cannabis use with respect to social life.